2003
DOI: 10.1021/np020583l
|View full text |Cite
|
Sign up to set email alerts
|

New Dimeric Morphine from Opium Poppy (Papaver somuniferum) and Its Physiological Function

Abstract: Together with bismorphine A (1), a new compound bismorphine B (2) was identified in the wounded capsules of Papaver somniferum. On the basis of analyses of the various spectral data, bismorphine B (2) was determined as a novel morphinan alkaloid, in which two morphine units are coupled through a biphenyl ether bond. When the physiological function of bismorphine B (2) in opium poppy was investigated, it was evident that this alkaloid more effectively cross-links cell wall polysaccharide pectins than bismorphin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…Bismorphine could be so evaluated as a defence response of the opium poppy. Morimoto et al (2003) together with bismorphine A identified also bismorphine B in the wounded capsules of Papaver somniferum.…”
mentioning
confidence: 84%
“…Bismorphine could be so evaluated as a defence response of the opium poppy. Morimoto et al (2003) together with bismorphine A identified also bismorphine B in the wounded capsules of Papaver somniferum.…”
mentioning
confidence: 84%
“…Host plants thicken their cell walls by producing large amounts of HCAAs, such as feruloyltyramine and feruloylputrescine, to prevent the spread of disease (Pushpa et al, 2014;Yogendra et al, 2014). Other chemical groups, such as benzylisoquinoline, flavonoid glycosides, and fatty acids, also play crucial roles in cell wall thickening (Morimoto et al, 2003;Franke et al, 2012;Gunnaiah et al, 2012), thus forming a physical barrier against P. infestans infection (Yogendra et al, 2015). Over the past two decades, significant efforts have also been undertaken to determine the metabolomic responses of potatoes to the pathogen.…”
Section: Introductionmentioning
confidence: 99%
“…Some dimeric morphine substances have been found in opium poppies using HPLC [17] and their physiological function in the poppies was discussed.…”
Section: Plant Materialsmentioning
confidence: 99%